Discontinuation and comparative effectiveness of dimethyl fumarate and fingolimod in 2 centers. Issue 4 (August 2018) - Vollmer, Brandi; Ontaneda, Daniel; Bandyopadhyay, Anasua; Cohn, Sam; Nair, Kavita; Sillau, Stefan; Bermel, Robert A.; Corboy, John R.; Fox, Robert J.; Vollmer, Timothy; Cohen, Jeffrey A.; Alvarez, Enrique; et al.
Abstract : Background: Dimethyl fumarate (DMF) and fingolimod (FTY) are approved oral disease-modifying therapies for relapsing multiple sclerosis (MS). Observational studies are valuable when randomized clinical trials cannot be done due to ethical or practical reasons. Two-site studies allow investigators to further ascertain external validity of previously examined treatment effect differences. Limited head-to-head 2-site studies exist comparing DMF and FTY. Methods: Patients prescribed DMF (n = 737) and FTY (n = 535) from 2 academic multiple sclerosis (MS) centers (Cleveland Clinic and University of Colorado) were identified. Discontinuation and disease activity endpoints were assessed using propensity score (PS) weighting. Covariates used in the PS model included demographics and clinical and MRI characteristics. Results: PS weighting demonstrated excellent covariate balance. Discontinuation was more common in DMF (44.2%) compared to FTY (34.8%) over 24 months (odds ratio [OR] 1.55, 95% confidence interval [CI] 1.21–1.99, p < 0.001). The leading cause for discontinuation was intolerability for both DMF (56.1% of DMF discontinuations) and FTY (46.2% of FTY discontinuations) (OR 1.65, 95% CI 1.21–2.25, p = 0.002). The proportion of patients with clinical relapses was low for both medications (DMF, 15.1%; FTY, 13.1%). There was no difference in the proportion of patients with relapses (OR 1.27, 95% CI 0.90–1.80, p = 0.174), gadolinium-enhancing lesions (OR 1.42, 95% CI 0.92–2.20, p = 0.114), or new T2 lesions on brain MRI (OR 1.13, 95% CI 0.83–1.55, p = 0.433). Conclusions: This combined analysis suggests DMF and FTY have similar effectiveness in a large, 2-site clinical population over 24 months. Discontinuation of both DMTs was common and occurred more frequently with DMF, largely driven by intolerability.